2020
DOI: 10.3803/enm.2020.301
|View full text |Cite
|
Sign up to set email alerts
|

Metabolically Healthy and Unhealthy Normal Weight and Obesity

Abstract: Increased fat mass is an established risk factor for the cardiometabolic diseases type 2 diabetes and cardiovascular disease (CVD) and is associated with increased risk of all-cause and CVD mortality. However, also very low fat mass associates with such an increased risk. Whether impaired metabolic health, characterized by hypertension, dyslipidemia, hyperglycemia, insulin resistance, and subclinical inflammation, may explain part of the elevated risk of cardiometabolic diseases that is found in many subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 53 publications
1
25
0
2
Order By: Relevance
“…This partly explains hyperimmune response to infectious insult including SARS-CoV-2 and adverse outcomes of COVID-19 in MUNW people. Another possible factor is reduced muscle mass characteristic of MUNW individuals [ 16 ]. Reduced muscle mass has been proposed to be independently associated with insulin resistance and increased susceptibility to adverse respiratory outcomes, including pneumonia and sepsis [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This partly explains hyperimmune response to infectious insult including SARS-CoV-2 and adverse outcomes of COVID-19 in MUNW people. Another possible factor is reduced muscle mass characteristic of MUNW individuals [ 16 ]. Reduced muscle mass has been proposed to be independently associated with insulin resistance and increased susceptibility to adverse respiratory outcomes, including pneumonia and sepsis [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…This observation directed much interest to metabolically unhealthy without obesity phenotypes. However, metabolically healthy with obesity phenotypes have also been observed [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many methods used to evaluate body fat distribution, such as computed tomography (CT) and magnetic resonance imaging (MRI), are expensive and not feasible in clinical practice. The concept of metabolic body composition status (MBCS), which may reflect different patterns of body fat distribution (9)(10)(11), has been proposed to describe six different phenotypes (12), namely metabolically healthy normal weight (MHNW), metabolically healthy overweight (MHOW), metabolically healthy obesity (MHO), metabolically unhealthy normal weight (MUNW), metabolically unhealthy overweight (MUOW), and metabolically unhealthy obesity (MUO). In recent years, several studies have indicated the importance of MBCS in assessing the risk of diabetes and cardiovascular disease (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…However, large epidemiological studies have shown that metabolically healthy obese individuals have greater all-cause mortality than metabolically healthy lean individuals [ 63 ], and that metabolically healthy obese individuals have greater odds of developing cancer than metabolically healthy lean individuals [ 64 ]. Conversely, there exist individuals with a BMI between 18.5 and 25 kg/m 2 who nevertheless exhibit elevated cardiometabolic risk factors with decreased skeletal muscle mass and elevated visceral fat mass, referred to as metabolically unhealthy normal-weight individuals [ 65 ], who have higher risk for diabetes [ 66 ], a three-folder high risk of all-cause mortality/cardiovascular disease [ 67 ], and an increased risk of cancer [ 58 ].…”
Section: Obesity's Link To Insulin Resistance and Hyperinsulinemiamentioning
confidence: 99%